Regulatory Volume Decrease in Neural Precursor Cells: Taurine Efflux and Gene Microarray Analysis - Hernández-Benítez, Reyna; Sedeño-Cortés, Adriana; Ramos-Mandujano, Gerardo; Pasantes-Morales, Herminia (Cellular physiology and biochemistry, 2014)
Background/Aims: Neural stem/ progenitor cells (NPCs) endure important changes in cell volume during growth, proliferation and migration. As a first approach to know about NPC response to cell volume changes, the Regulatory Volume Decrease (RVD) subsequent to hypotonic swelling was investigated. Methods: NPCs obtained from the mesencephalon and the subventricular zone of embryonic and adult mice, respectively, were grown and cultured as neurospheres. Cell volume changes were measured by large-angle light-scattering and taurine efflux by [ 3 H]-taurine. Expression of genes encoding molecules related to RVD was analysed using a DNA microarray obtained from NPC samples. Results: Embryonic and adult NPCs exposed to osmolarity reduction (H15, H30, H40) exhibited rapid swelling followed by RVD. The magnitude, efficiency and pharmacological profile, of RVD and of [ 3 H]-taurine osmosensitive efflux were comparable to those found in cultured brain cells, astrocytes and neurons. The relative expression of genes encoding molecules related to volume regulation, i.e. K + and Cl - channels, cotransporters, exchangers and aquaporins were identified in NPCs. Conclusion: NPCs show the ability to respond to hypotonic-evoked volume changes by adaptative recovery processes, similar to those found in other cultured brain cells. Genes related to molecules involved in RVD were found expressed in NPCs.